Analisis Kandungan Minyak dalam Air dan Sedimen di Perairan Pantai Rupat Utara dan Selatan - Al Usman; Syahril Nedi; Bintal Amin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
A study on oil content in water and sediment was conducted in December 2015. The purpose of the study was to provide baseline data on environmental quality of Northen and Southern parts of Rupat Island Coastal Waters. The results of this study showed that average oil content in water North Rupat is 0.1403 ppm and average oil content in the sediment is 5402.5833 ppm. Meanwhile the average oil content in the of South Rupat is 0.0599 ppm and average oil content in the sediment is 6540.3333 ppm. According to standart value of sea water quality, oil content in the water has not exceeded the threshold value ( < 5 ppm ), whereas the oil content of sediment has exceeded the threshold value ( > 100 ppm ).Key words :Oil, Sediment, Water, Rupat